Effect of Cr Addition on Magnetic Properties and Corrosion Resistance of Optimized Co and Fe-Based Amorphous Alloys - Han, Jonghee; Hong, Jihyun; Kwon, Seoyeon; Choi-Yim, Haein (MDPI, 2021)
In the Fe-Co alloy system, the addition of Cr improves the glass-forming ability (GFA) with superior soft magnetic properties such as high saturation magnetization (M-s) and low coercivity (H-c). In addition, Cr is considered to be an important factor for improving the corrosion resistance of Fe-based amorphous alloy. Therefore, in the present study, we investigated the GFA, soft magnetic properties, and corrosion resistance of the as-spun ribbons in [Co0.075Fe0.675B0.2Si0.05](100-x)Cr-x (x = 0-8) alloy system. The ribbons were produced using the melt-spinning technique and were characterized by X-ray diffraction, differential scanning calorimetry, thermomechanical analysis, and vibrating sample magnetometer. The Co-Fe-B-Si-Cr alloys exhibited high thermal stability and a high M-s of 0.93-1.53 T. Corrosion properties were evaluated by cyclic voltammetry. The addition of Cr improved the corrosion resistance of the alloys. The alloys with a higher Cr content exhibited a higher corrosion resistance. The optimum combination with soft magnetic properties and corrosion resistance of Fe-co based amorphous alloys can be utilized for extensive fields of application through a variation of Cr contents.